ANALISIS KECERDASAN MAJEMUK PADA BUKU AJAR SISWA KELAS III KURIKULUM 2013 - Alma Eka Rakhmawati; Muhamad Rizki Mubarok; Dede Indra Setiabudi (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
This study aims to: 1) describe the multiple intelligences seen in student activities in the third grade 2013 curriculum; and 2) explain the development of multiple intelligences that have not been seen in student activities in the textbooks for class III students of the 2013 curriculum. The research conducted is included in the type of qualitative research. The data collection method used is literature study and discussion with colleagues. The results of the analysis of the thematic book for class III Objects Around Me 2013 curriculum that aspects of multiple intelligences have not been raised or developed as a whole. This can be seen in sub-theme 1 of intelligence that appears more dominant, namely linguistic intelligence and interpersonal intelligence, while intelligence that is not at all raised is naturalist intelligence. In sub-theme 2, visual-spatial intelligence and interpersonal intelligence are dominantly developed, and musical intelligence is not developed at all. Meanwhile, the 3 intelligence sub-themes that often appear are linguistic intelligence and intrapersonal intelligence, besides that musical intelligence has not yet been raised. And sub-theme 4 has visual-spatial intelligence and interpersonal intelligence that are often raised in student activities, the intelligence that is still lacking and has not been raised is musical intelligence. So that the results of the study can be concluded that in general the activities contained in the class III curriculum 2013 textbooks are able to develop eight intelligences.